Craniocerebral trauma characterization in hospitalized patients. Cienfuegos, 2018-2020 - Aymée Marrero Gil; Ernesto López Cabrera (Medisur)
Foundation: traumatic brain injury is one of the main causes of morbidity and mortality in the child population; it involves several physical, social and cognitive alterations in survivors. Objective: to characterize pediatric patients admitted for craniocerebral trauma. Methods: an observational, descriptive, cross-sectional study was carried out in patients aged 0 to 17 years old, admitted for craniocerebral trauma from January 2018 to December 2020. The data were collected from the individual medical history and provincial statistical registry. Results: the age group that contributed the most patients was between 1 and 9 years old with 52.6%. The male sex predominated (65.6%). Falls were the main cause of trauma (64.8%). Regarding the triennium studied, the year 2020 showed a decrease in cases. 45.7% of the cases came from the Cienfuegos municipality. 90.9% of patients had mild neurological impairment upon admission. Focal lesions represented 84.4% of the TBI-specific lesions found. Conclusions: craniocerebral trauma was more frequent in male sex and urban origin transitional and schoolchildren. Falls were the most relevant cause and neurological condition was mild in the majority of patients. There were no complications or deaths.